Forensic audit of public debt in the financial control system of Ukraine - Hanna Filatova; Nataliia Ovcharova; Olena Kravchenko (Accounting and Financial Control, 2025)
Forensic audit of public debt is an important tool for ensuring financial transparency and effective public finance management. In the context of Ukraine, given the difficult economic situation and high level of public debt, the use of forensic audit is of particular importance. The study aims to conduct a forensic audit of Ukraine’s public debt by assessing the consistency of financial statements of key government agencies, identifying discrepancies, and evaluating their potential impact on financial stability. The methodology includes a cross-analysis of financial data from the Ministry of Finance of Ukraine, the National Bank of Ukraine, the Accounting Chamber of Ukraine, and the State Treasury Service. The study also includes an assessment of compliance with international public sector auditing standards (ISSAI, IPSAS, and OECD principles). The results show discrepancies in key public debt indicators between the different reporting institutions, with variations in total debt, debt service costs, and classification methodologies. Key findings indicate inconsistencies in the timing of data publication, differences in accounting methodology, and gaps in debt transparency. These discrepancies pose risks to the effectiveness of financial policy, external creditworthiness, and overall macroeconomic stability. The study concludes that strengthening coordination between government agencies and integrating forensic audit mechanisms into the system of regular financial oversight is necessary to increase the transparency of public debt and reduce financial risks. The proposed recommendations will help to improve fiscal management and ensure the reliability of financial reporting in Ukraine's public debt management system. Acknowledgment Prepared as part of a research project 101127602-EUEPDM-ERASMUS-JMO-2023-HEI-TCH-RSCH – "EU experience in public debt management: conclusions for Ukraine in the war and post-war period". However, the views and opinions expressed are those of the authors alone and do not necessarily reflect the views of the European Union or the European Executive Agency for Education and Culture (EACEA). Neither the European Union nor EACEA can be held responsible for them.